Evidentiary Challenges in Cases of Sexual Abuse Involving Children (Legal journal - Research in Legal and Social Sciences, 2024)
The article focuses its analysis on the evidentiary challenges in cases of sexual abuse against children, defined as any act carried out by an adult or adolescent who uses a child to stimulate or gratify themselves sexually. According to González (2023), it is termed ‘abuse’ because, whether such acts are committed with or without the child’s consent, they involve actions for which the child lacks the maturity and cognitive development necessary to discern and evaluate their consequences. In most cases, the sole evidence is the victim’s testimony. However, it is well established that corroboration of all evidentiary elements is required. Nonetheless, these acts are typically committed in private, without witnesses, and without additional indicators that could definitively demonstrate the occurrence of the act and the corresponding authorship. Regarding methodology, the study adopts a mixed-method approach with a non-experimental, documentary design and a descriptive scope. The conclusion highlights the challenges in obtaining sufficient evidence. However, it is possible to develop investigative techniques that lead to additional corroborative evidence, which can be valuable for assessment by the sentencing court.
Keywords: sexual abuse; evidentiary difficulty; valuation